Cocrystallization with acetylene. The 1 : 1 complex with benzene: Crystal growth, x-ray diffraction and molecular simulations - Clark, Timothy; et al. (Helvetica Chimica Acta, 2003)
The crystal structure of an unusual 1 : 1 molecular complex between benzene and acetylene, two very small and apolar molecules, has been determined by X-ray-analysis of crystals grown by first mixing the two liquids under conditions of low temperature and high pressure in a capillary, followed by repeated zone melting to form crystals directly on the goniometer head of a diffractometer. Each acetylene molecule is clamped between two parallel benzene rings, with its molecular axis apparently perpendicular to the benzene planes. Closer inspection of thermal-motion data from the diffraction experiment suggests that the acetylene molecule undergoes a wobbling, or precession, motion between the two rings so that it is perpendicular to them only in a time-averaged sense. The results of quantum-chemical calculations on isolated molecular dimers and trimers support this conclusion. In addition, the calculation of separate coulombic, dispersion, polarization and repulsion contributions to intermolecular bonding reveals that the C-H ... pi-bond interaction between acetylene and benzene in a T-shaped dimer consists of a mixture of coulombic and polarization interactions. In the benzene-acetylene cocrystal, its magnitude is quantitatively comparable with that of other dispersive interactions. 5.4 ns Molecular-dynamics simulations of the liquid mixture reveal that the two components are persistently miscible, a possible key to the formation of the cocrystal. No structure is, however, observed in the solution during the relatively short simulation time.